A Molecularly Characterized Preclinical Platform of Subcutaneous Renal Cell Carcinoma (RCC) Patient-Derived Xenograft Models to Evaluate Novel Treatment Strategies - Gürgen, Dennis; Becker, Michael; Dahlmann, Mathias; Flechsig, Susanne; Schaeffeler, Elke; Büttner, Florian A.; Schmees, Christian; Bohnert, Regina; Bedke, Jens; Schwab, Matthias; Wendler, Johann J.; Schostak, Martin; et al. (Frontiers in Oncology, 2022)
Renal cell carcinoma (RCC) is a kidney cancer with an onset mainly during the sixth or seventh decade of patient’s life. Patients with advanced, metastasized RCC have a poor prognosis. The majority of patients develop treatment resistance towards Standard of Care (SoC) drugs within months. Tyrosine kinase inhibitors (TKI) are the backbone in first line therapy and have been partnered by an immune checkpoint inhibitor recently. Despite most recent progress, the development of novel therapies targeting acquired TKI resistance mechanisms in advanced and metastatic RCC remains a high medical need. Preclinical models with high translational relevance can significantly support the development of novel personalized therapies. It has been demonstrated that patient-derived xenograft (PDX) models represent an essential tool for the preclinical evaluation of novel targeted therapies and their combinations. In the present project, we established and molecularly characterized a comprehensive panel of RCC PDX models with well conserved molecular and pathological features over multiple passages. Drug screening towards four SoC drugs targeting VEGF and PI3K/mTOR pathways revealed individual and heterogeneous response profiles in those models, very similar to observations in patients. As unique features, our cohort includes PDX models from metastatic disease and multi-tumor regions from one patient, allowing extended studies on intra-tumor heterogeneity. The PDX models are further used as basis for developing corresponding in vitro cell culture models enabling advanced high-throughput drug screening in a personalized context. PDX models were subjected to next generation sequencing (NGS). Characterization of cancer-relevant features including driver mutations or cellular processes was performed using mutational and gene expression data in order to identify potential biomarker or treatment targets in RCC. In summary, we report a newly established and molecularly characterized panel of RCC PDX models with high relevance for translational preclinical research.